2003
DOI: 10.1590/s0100-84042003000100004
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and anatomy of the fruit and seed in development of Chorisia speciosa A. St.-Hil. - Bombacaceae

Abstract: -(Morphology and anatomy of the fruit and seed in development of Chorisia speciosa A. St.-Hil. -Bombacaceae). The structure of the fruit and seed in development of Chorisia speciosa are described with the main purpose of clarifying the origin and nature of the hairs that cover the seeds and aiding future taxonomical and ecological studies of the group. The fruit is an ellipsoid loculicide capsule and presents the exocarp formed by 7-10 cells layers, with very thick walls and evident simple pits. A great number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The localization of POD activity in correspondence of the vascular bundles was probably linked with the role of this enzyme in the process of lignin biosynthesis (Lee and others 2007), a fundamental step of xylem formation. A similar role could explain the presence, at early developmental stages, of peroxidases in correspondence of the seed hypostase, which is constituted by cells with lignified walls (Marzinek and Mourão 2003), and also in seed teguments during the late stages of growth. The POD activity detected in correspondence of the seed locules could contribute both to the control of the concentration of the IAA produced by the seeds and to the protection of these organs from reactive oxygen species, that are key components of seed biology (Bailly 2004).…”
Section: Discussionmentioning
confidence: 78%
“…The localization of POD activity in correspondence of the vascular bundles was probably linked with the role of this enzyme in the process of lignin biosynthesis (Lee and others 2007), a fundamental step of xylem formation. A similar role could explain the presence, at early developmental stages, of peroxidases in correspondence of the seed hypostase, which is constituted by cells with lignified walls (Marzinek and Mourão 2003), and also in seed teguments during the late stages of growth. The POD activity detected in correspondence of the seed locules could contribute both to the control of the concentration of the IAA produced by the seeds and to the protection of these organs from reactive oxygen species, that are key components of seed biology (Bailly 2004).…”
Section: Discussionmentioning
confidence: 78%
“…These cells had very thick walls with simple holes visible. The mesocarp derived from ovarian mesophyll that had fibrous because of the differentiation of fibers around the vascular bundles (Marzinek and Mourao 2003). The mesocarp was derived from parenchymatous cells, which were large, isodiametric, and thin walls (Retamales et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that the mesocarp contained small granules that consistent with the reported by Murwani (2012) for Annona muricata, A. reticulata, and A. squamosa who indicated that the small granules in the mesocarp were starch because when they were reacted with KI3 (potassium iodide) solution they turn blue (Murwani 2012). The endocarp was composed of the ventral epidermis of the ovary wall, whose cells undergo a gradual elongation and lignification (Marzinek and Mourao 2003).…”
Section: Discussionmentioning
confidence: 99%